2015
DOI: 10.1049/iet-map.2014.0416
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐form and dispersive model considerations for relative permittivity extraction at millimetre‐wave frequencies

Abstract: This study provides a simple broadband method for determining the dielectric properties of laminate substrate materials used in integration and packaging solutions for commercial millimetre‐wave applications. Relative permittivity and loss tangent are extracted from coplanar lines using closed‐form equations that account for as‐fabricated transmission line dimensions. The method is applied to a low loss substrate alumina and further tested on glass impregnated epoxy resin materials with metals that have an app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A few 24 GHz antennas have also been reported, but they are also designed on Rogers substrates and use expensive material for lens design. Recently, a published research article [9] reported the characterization of low-cost FR4 based substrates. According to this analysis, the FR408 substrate shows decent performance at 24 GHz, which was confirmed by calculating its electrical parameters by designing a ring resonator at 24 GHz on the FR408HR substrate.…”
Section: Introductionmentioning
confidence: 99%
“…A few 24 GHz antennas have also been reported, but they are also designed on Rogers substrates and use expensive material for lens design. Recently, a published research article [9] reported the characterization of low-cost FR4 based substrates. According to this analysis, the FR408 substrate shows decent performance at 24 GHz, which was confirmed by calculating its electrical parameters by designing a ring resonator at 24 GHz on the FR408HR substrate.…”
Section: Introductionmentioning
confidence: 99%